1986
DOI: 10.1007/bf00824333
|View full text |Cite
|
Sign up to set email alerts
|

An experimental and morphological analysis of the tail bud mesenchyme of the chick embryo

Abstract: In the chick embryo, the tail bud reaches its maximum length at about stage 22 of Hamburger and Hamilton, after which it starts to regress. By this stage the neural tube and notochord extend right to the tip of the tail, but the somites do not do so, the terminal tail bud mesoderm never becoming segmented. The investigation is concerned with analysing why this mesoderm fails to segment. When tail buds were explanted to the chorio-allantoic membrane, they continued to form somites only until the "correct" numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 18 publications
2
37
0
Order By: Relevance
“…As the presomitic mesoderm shortens during axial elongation (Gomez et al, 2008;Sanders et al, 1986), RA from the most recently formed somites might now be able to reach tail bud cells, thereby ending this process. This possibility is supported by the downregulation of Fgf8 in the mouse tail by E12.5 (Cambray and Wilson, 2007) and in the chick at HH26/HH27 (I.O.-M. and K.G.S., unpublished) just prior to the end of axis elongation.…”
Section: Cessation Of Axis Elongationmentioning
confidence: 99%
See 1 more Smart Citation
“…As the presomitic mesoderm shortens during axial elongation (Gomez et al, 2008;Sanders et al, 1986), RA from the most recently formed somites might now be able to reach tail bud cells, thereby ending this process. This possibility is supported by the downregulation of Fgf8 in the mouse tail by E12.5 (Cambray and Wilson, 2007) and in the chick at HH26/HH27 (I.O.-M. and K.G.S., unpublished) just prior to the end of axis elongation.…”
Section: Cessation Of Axis Elongationmentioning
confidence: 99%
“…This might elicit a slowing down of the cell cycle and the eventual cell cycle exit of progenitor cell populations. Conversely, the loss of Fgf8 also coincides with high levels of cell death in the late-stage chick tail bud (Hirata and Hall, 2000;Mills and Bellairs, 1989;Sanders et al, 1986;Yang et al, 2006), raising the possibility that a local increase in endogenous RA triggers apoptosis to terminate axis extension.…”
Section: Cessation Of Axis Elongationmentioning
confidence: 99%
“…In addition, for the formation of various structures during morphogenesis, cell death occurs according to precise temporal sequences and spatial patterns and is considered to play a key role by elim- inating unnecessary cells to achieve complex histogenesis and organogenesis. For example, cell death is involved in remodeling the embryonic tail bud in humans (Kunimoto, 1918;Wittman et al, 1972;Fallon and Simandl, 1978), mice (Wittman et al, 1972;Schoenwolf, 1984;Tam, 1984), rats (Butcher, 1929;Gajović et al, 1989Gajović et al, , 1993Qi et al, 2000b), and chicks (Klika and Jelinik, 1969;Van Horn, 1971;Schoenwolf, 1981;Sanders et al, 1986;Mills and Bellairs, 1989;Miller and Briglin, 1996). Several investigators have indicated that cell death is involved in removal of the tailgut in chicks (Van Horn, 1971), rats (Š vajger et al, 1985), and humans (Fallon and Simandl, 1978).…”
Section: Spatiotemporal Distribution Of Apoptosis In Cloacal Developmentmentioning
confidence: 99%
“…Formation of the neural tube in the tail bud results from cavitation of the medullary cord, and is distinct from primary neurulation, which occurs by the folding and fusion of the dorsal edges of the neural plate (Criley, 1969;Kilka and Jelinek, 1969;Schoenwolf and Delongo, 1980). The nascent embryonic chick tail subsequently undergoes reduction and remodeling by selective proliferation, involution and cell death (Lanot, 1980;Schoenwolf, 1981;Sanders et al, 1986;Uehara and Ueshima, 1988;Miller and Briglin, 1996). Despite these differences, similarities in gene expression patterns in the primitive streak and tail bud (Gont et al, 1993;Gofflot et al, 1997;Knezevic et al, 1998;Cambray and Wilson, 2007), and the analysis of morphogenic movements in the streak and tail bud (Pasteels, 1937;Gont et al, 1993;Catala et al, 1995;Kanki and Ho, 1997;Knezevic et al, 1998), reveal many commonalities between these two processes in several vertebrate species.…”
Section: Introductionmentioning
confidence: 99%